Integrating ecosystem services into crop protection and pest management: Case study with the soil fumigant 1, 3‐dichloropropene and its use in tomato production in Italy. (7th May 2016) - Deacon, Samantha; Alix, Anne; Knowles, Steve; Wheeler, James; Tescari, Enzo; Alvarez, Lara; Nicolette, Joseph; Rockel, Mark; Burston, Peter; Quadri, Giorgia
ABSTRACT: Ecosystems provide the conditions for producing food, regulating water, and providing wildlife habitats; these, among others, are known as ecosystem services (ESs). Food production is both economically and culturally important to southern European farmers, particularly in Italy where farmers grow flavorsome tomatoes with passion and pride. Growers rely on pesticides for crop protection, the potential environmental impact of which is often questioned by regulators and other stakeholders. The European regulatory system for the approval of pesticides includes a thorough evaluation of risks to the environment and is designed to be protective of ecosystems. The consideration of ESs in environmental decision making is a growing trend, and the present case study provides an example of how ESs evaluation could be used to enhance agricultural practices and regulatory policy for crop protection. By attacking plant roots, nematodes may affect the growth and yield of fruit and vegetable crops, and the income earned by farmers at harvest time. Available solutions include chemical treatments such as 1, 3‐dichloropropene (1, 3‐D), physical treatments (solarization), and biological treatments (biofumigation). In order to characterize the risks and benefits associated with the use of 1, 3‐D in crop protection, ESs and socioeconomic analyses were applied to its use in the control of nematodes in tomato cultivation in southern Italy. The present study confirmed the benefits of 1, 3‐D to tomato production in Italy, with significant positive effects on production yields and farm income when compared to limited and transient potential impacts on services such as soil function. It was confirmed that 1, 3‐D allows farm income to be maintained and secures tomato production in these regions for the future. Integr Environ Assess Manag 2016;12:801–810. © 2016 SETAC Key Points: Growers rely on pesticides for crop protection, the potential environmental impact of which is often questioned by regulators and other stakeholders. This case study provides an example of how ecosystem service evaluation could be used to enhance agricultural practices and regulatory policy for crop protection. The study confirmed the benefits of 1, 3‐dichloropropene (1, 3‐D) to tomato production in Italy, with significant positive effects on production yields and farm income when compared to limited and transient potential impacts on services such as soil function. It was confirmed that 1, 3‐D allows farm income to be maintained and secures tomato production in these regions for the future.